Inventing the “Poétesse”: New Approaches to French Women Romantic Poets - Boutin, Aimée (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractWomen poets of the nineteenth century remain for the most part marginalized in the study of French Romanticism, despite the historical fact that women turned to poetry in increasing numbers during the July Monarchy. The poetess’s enduringly ambiguous situation is reflected in the linguistic instability of the terminology used to designate her. This essay takes as its starting point the linguistic uncertainty surrounding the term "poétesse" in the nineteenth century and compares it to Anne Mellor’s definitions of the poetess and the female poet. In a survey of French Romantic poetesses (Desbordes-Valmore, Tastu, Gay, Mercoeur, Ségalas), Mellor’s distinction between two traditions proves to be untenable, as poetesses straddle the fine line between domesticity and social engagement. Ultimately, Mellor’s definition of the poetess in opposition to the female poet does however resonate with French women poets’ critical reception: the invention of the poétesse has largely obscured the critical assessment of women poets’ social engagement.